Biologia populacional de espécies comercialmente importantes de lutjanídeos (Teleostei: Lutjanidae) capturados no Estado do Ceará, Brasil - Pinheiro, Waslley Maciel (2023)
Lutjanids are commercially important fishery resources, especially in the Northeast, where lane snapper Lutjanus synagris (Linnaeus, 1758), mutton snapper Lutjanus analis (Cuvier, 1828), and yellowtail snapper Ocyurus chrysurus (Bloch, 1791), are among the species with the highest capture volumes. However, knowledge regarding their life histories is still limited in Ceará, particularly in terms of reproductive biology and age and growth studies. The production and updating of reproductive and growth parameters are crucial as they are influenced by fishing pressure and essential for efficient fisheries management. The objectives of this research were to identify knowledge gaps for these three species through a systematic review of reproduction and age and growth studies and to describe and update population parameters for L. synagris and L. analis, captured by an artisanal fleet based in Mucuripe Embayment, Fortaleza, Ceará. The systematic review encompassed articles published in the 21st century (from 2001 to 2023), based on searches conducted on the following platforms: CAPES Periodicals, Science Direct, Web of Science, Scopus, Google Scholar, and Scielo. Out of the 1,883 articles found, 105 were considered for full reading, including 36 on L. synagris, 42 on L. analis, and 27 on O. chrysurus. The results indicate a lack of standardization in estimates of the size at first sexual maturity (L50) for these species, the need to estimate this parameter for grouped sexes, and knowledge gaps in reproduction and age and growth studies, particularly for L. analis and O. chrysurus. Population biology studies were conducted for L. synagris and L. analis. Landings were monitored monthly, covering the period from January to December 2019. Individuals were measured (cm), weighed (kg), and had their gonads and otoliths extracted for subsequent population parameter analysis. For L. synagris, out of the 120 sampled individuals, 64 were males and 56 were females, with a sex ratio of 1.1:1 (M:F), which did not significantly differ from the expected sex ratio. GSI, HSI, and monthly frequencies of sexually mature females were uniform, indicating year-round spawning for the species. The length at first sexual maturity (L50) was 32.2 cm for grouped sexes, 32 cm for females, and 33.5 cm for males. The species exhibited an average fecundity of 207,000 oocytes and asynchronous oocyte development, resulting in batch spawning. The growth coefficient (K) was 0.23 year−1, the theoretical asymptotic length (L∞) was 45.27 cm TL, and the growth performance index (φ') was 2.84. The average age at first sexual maturity (A50) was 5.43 years. The results suggest that the population of L. synagris in Ceará showed some stability in terms of reproductive and age and growth parameters and may be subject to low fishing effort by the artisanal fleet in Mucuripe Embayment, requiring continuous monitoring of fish landings to provide updated information for comparison in future population structure studies, with the aim of ensuring species conservation. For L. analis, In total, 120 specimens were recorded, 61 males and 59 females, resulting in a sex ratio of 1.03:1 (M:F), which did not significantly differ from the expected sex ratio. The results of GSI, HSI, and monthly frequency of mature females indicate that the species exhibits year-round spawning, with a peak mainly in the dry season in Ceará, particularly in the month of September. The length at first sexual maturity (L50) was 35.4 cm for grouped sexes, 35.1 cm for females, and 35.8 cm for males. The species displayed an average fecundity of 194,000 oocytes and asynchronous oocyte development, resulting in batch spawning. This represents the first study in Ceará to estimate reproductive parameters for L. analis. The species exhibits favorable reproductive parameter indices in the study area, suggesting the need for continuous monitoring of landings to assess potential fluctuations in the population dynamics of this species in Ceará. These species are of significant commercial importance to the State, highlighting the need for effective fisheries management that ensures both sustainable fisheries productivity of these resources and the replenishment of stocks. It is suggested that future research should address life history parameters collectively, along with the implementation of monitoring programs for lane snapper, mutton snapper and other lutjanid species, with the aim of assessing whether fishing pressure negatively impacts these species, as this activity may take some time to generate cumulative impacts on these populations and lead to stock overexploitation.